Forecasting Cyber Threat Landscapes in Indonesia (2025-2026): A Predictive Analysis Using the MITRE ATT&CK Framework - Adji Kusuma; Suhirwan; Agus H Sulistyono Reksoprodjo (International Journal of Education, Vocational and Social Science, 2026)
As Indonesia accelerates its digital transformation under the "Making Indonesia 4.0" initiative, the national cyber threat landscape is evolving from opportunistic attacks to sophisticated, targeted campaigns. This study presents a predictive analysis of cyber attack trends in Indonesia for the period of 2025-2026. By leveraging historical incident data from the National Cyber and Crypto Agency (BSSN) and global threat intelligence, we map projected adversary behaviors onto the MITRE ATT&CK Framework. The analysis indicates a significant surge in Supply Chain Compromises (T1195), Ransomware-as-a-Service (T1486), and Cloud Infrastructure Exploitation. The findings suggest that Indonesian critical infrastructure, particularly in the financial and e-government sectors, will face heightened risks from Advanced Persistent Threat (APT) groups. This paper proposes a proactive defense strategy centered on Threat Hunting and Zero Trust Architecture to mitigate these forecasted risks.